Risk of preterm birth after treatment for cervical intraepithelial neoplasia among women attending colposcopy in England: retrospective-prospective cohort study. (16th August 2012) - Castanon, Alejandra; Brocklehurst, Peter; Evans, Heather; Peebles, Donald; Singh, Naveena; Walker, Patrick; Patnick, Julietta; Sasieni, Peter
Abstract : Objective To explore the association between preterm delivery and treatment at colposcopy. Design Retrospective-prospective cohort study using record linkage. Setting 12 National Health Service hospitals in England. Participants Women who had a cervical histology sample taken between 1987 and 2009. These women were linked by hospital episode statistics to hospital obstetric records between 1998 and 2009 for the whole of England to identify singleton live births between 20-43 gestational weeks before or after cervical histology. Main outcome measures Proportion of preterm births (<37 weeks); the relative risk for the strength of association between preterm births and treatment for cervical intraepithelial neoplasia. Results 18 441 singleton births occurred: 4176 before histology and 14 265 after histology. Of the singleton births after histology, 9.0% (n=1284) were preterm compared with 6.7% of all births in England over the same period (excess risk 2.3 per 100 births, 95% confidence interval 1.8% to 2.8%). Among first births after histology, the adjusted relative risk associated with previous treatment was 1.19 (95% confidence interval 1.01 to 1.41); among first births before histology the relative risk associated with subsequent treatment was 1.47 (1.05 to 2.05). Combining these, the relative risk associated with treatment adjusted for timing relative to histology was 0.91 (0.66 to 1.26) corresponding to an absolute difference of −0.25 (−2.61 to 2.11) per 100 singleton births. Among 372 women who gave birth both before and after treatment, there were 30 preterm births after treatment and 32 before treatment (relative risk 0.94, 0.62 to 1.43). Conclusion The risk of preterm delivery in women treated by colposcopy in England was substantially less than that in many other studies, predominantly from Nordic countries. The increased risk may be a consequence of confounding and not caused by treatment. Although this study is reassuring for large loop excision of the transformation zone overall, it is possible that deep conisation or repeated treatment leads to an increased risk of preterm delivery.